Metastatic Colorectal Cancer Patient With Microsatellite Stability and BRAFV600E Mutation Showed a Complete Metabolic Response to PD-1 Blockade and Bevacizumab: A Case Report - Fang, Chongkai; Lin, Jietao; Zhang, Tao; Luo, Jiajun; Nie, Duorui; Li, Meng; Hu, Xue; Zheng, Yating; Huang, Xuewu; Xiao, Zhiwei (Frontiers in Oncology, 2021)
A vast majority of colorectal cancer (CRC) patients with microsatellite stability (MSS) or proficient mismatch repair (pMMR) are refractory to immunotherapeutic strategies. The current research focusses on the combined treatment strategies for identification and optimization in order to improve the efficacy of immunotherapy among patients with microsatellite stability (MSS), who account for the majority of metastatic colorectal cancer (mCRC) cases. mCRC patients harboring MSS and the BRAFV600E mutation show a worse prognosis and barely benefit from immunotherapy. In this report, we discuss the case of a mCRC patient with MSS and BRAFV600E mutation, who exhibited significant response to the combined treatment with nivolumab and bevacizumab, and has been exhibiting a progression-free survival (PFS) of more than 17 months. Our findings indicate that combined anti-angiogenic therapy can improve the efficacy of immunotherapy, which results in the prolong survival of the patient. This is a case report on MSS and BRAFV600E colorectal cancer which presents with a response to immunotherapy and anti-angiogenic therapy.